Case Report: Durable Complete Response After Combined Immunotherapy Following Resection of Primary Tumor in a Gallbladder Cancer Patient With Distant Metastatic Lymph Nodes of Favorable Immune-Microenvironment - Yi, Bin; Zhao, Zhikun; Dong, Hui; Yuan, Lei; Wu, Yingjun; Xu, Yun; Jiang, Xiaoqing; Sun, Chao; Wu, Dongfang; Xiao, Yajie (Frontiers in Immunology, 2022)
Background Metastatic gallbladder carcinoma (GBC) is one of the most aggressive malignancies. As GBC is usually diagnosed with distant metastases, only a few patients can receive R0 resection and the relapse rate remains high. Programmed cell death protein 1 (PD-1) blockade therapy has provided encouraging long-term outcomes in a subset of patients in many cancers. However, the data on efficacy of PD-1 blockade in GBC are very limited. Case Presentation We herein reported a stage IVB GBC patient with localized primary tumor and distant lymph node metastasis. Except for the unresectable multiple metastatic nodes including distant nodes, a complete resection of primary tumor en bloc with partial segment 4B+5 was performed. Tumor tissues of primary tumor and one metastatic lymph node were collected to perform whole-exome sequencing, RNA-seq, and immunohistochemistry. Low TMB (5.38 muts/Mb), low MSI (<20%), and negative PD-L1 expression (TC0) were observed in the primary tumor. Likewise, low TMB (5.44 muts/Mb), low MSI (<20%), and low PD-L1 expression (TC2) presented in the metastatic lymph node. Besides, low genetic intratumor heterogeneity exhibited between the primary and metastatic tumors in this patient. In contrast to the primary tumor, higher-level CD8+ T cell infiltration was revealed in the tumor microenvironment of the metastatic lymph node. Then, chemo-immunotherapy using S1 and anti-PD-1 antibody pembrolizumab was administrated as the first-line treatment for the residual metastatic nodes. Complete response was achieved after 7 courses and has lasted for 32 months up to present. Additionally, blood samples during treatment were further analyzed for immune repertoire sequencing, showing that several T cell receptor clones in metastatic lymph node were predominant in blood during the combined anti-PD-1 treatment. Conclusions Chemo-immunotherapy may provide a potential curative option for the lymph node metastases of gallbladder cancer. The low intratumor heterogeneity and high level of infiltrating CD8+ T-cells in metastatic node might be indispensable to the durable complete response in this patient.